Use of a synthesized mathematical model to describe the probability of curing early-stage breast cancer - L. Ya. Klepper; I. A. Gladilina; V. L. Ushkova; O. V. Kozlov; I. V. Vysotskaya (Опухоли женской репродуктивной системы)
Breast cancer (ВС) is a common malignant disease of the female reproductive system. Currently we have many treatment strategies given location depending on the clinical data. Radiation therapy is an important component in a comprehensive program of treatment for ВС. Despite the fact that often use a single dose fractionation regime 1.8–2 Gy daily fractions to a total of 50 Gy in 5 weeks, do not run out to try to find new modes of fractionation. According to published research results hypofractionated regimes, we can conclude that the approaches to the value of the dose per fraction,the number of fractions and the time of treatment differ. Dose per fraction ranged from 2.66 to 3.2 Gy, and more recently have been tested modes with a single dose of 6 Gy. Empirical data from these studies are important, but must also be aware of the possibility of applying mathematical methods for computing the probability of cure of the tumor and the occurrence of radiation complications.It is necessary for an individual approach to each patient, picking up for some clinical cases the optimal mode of fractionation. In addition, the search continues and improvement fractionation regimes, and the results of clinical trials can tell a lot about how good the chosen model. In work the opportunity of application of the synthesized mathematical model (SM model), intended for description of NTCP, to the description of probability of local treatment of early stages of the ВС.